Middle Miocene drowned ramp in the vicinity of Marija Bistrica (Northern Croatia) (Rudarsko-geološko-naftni zbornik, 2018)
Fossiliferous Middle Miocene deposits from the surroundings of Marija Bistrica (north-east of Zagreb) transgressively overly older pre-Cenozoic bedrocks. Fossils from shallow marine environments are in most cases preserved as bioclasts, while deep marine calcareous oozes characterize the pelagic marls. The age of the transgressive sequence is estimated on the basis of planktic biota from marls (foraminifera, nannoplankton and pteropods) as the Badenian NN5 Nannozone. The following palaeoenvironments can be distinguished or presumed on the basis of biota and sedimentary features: (1) beach characterized by polymictic conglomerates with rhodolith-rich carbonate matrix; (2) oyster banks, recognized from secondarily found oyster clusters; (3) lagoons marked with compact bioclastic deposits and rhodolith-halimeda assemblage; (4) patch-reefs recognized from the surrounding bioclastic deposits; (5) shallow subtidal mäerl beds preserved as loose bioclastic deposits and (6) distal slope argillaceous marls with pelagic biota. Palaeoenvironmental analyses indicate rapid drowning, most probably corresponding to the transgression during the Middle Badenian TB 2.4 3rd order transgressive-regressive sequence.